Toxoplasmosis y amigdalitis. - TORI TORI, Carlos (2013)
Acquired toxoplasmosis is a widespread, usually asymptomatic zoonotic infection caused by an intracellular protozoan parasite Toxoplasma gondii. Due to its predilection for parenchymal cells and those of the reticuloendothelial system, involvement of the lymphoid tissue is the most common clinical finding. This patient presented with abdominal pain predominantly in the right lower quadrant, which dissapeared promptly, painful cervical lymph node involvement and a severe case of acute exudative tonsilitis which is exceedingly unusual. Diagnostic levels of IgM Against Toxoplasmosis highly suggests that the patient had acute or a very recent infection with the protozoan. It is difficult to determine whether the parasite was the cause of her illness or that she acquired a concomitant viral infection, like adenovirus. It would had been important and diagnostic to do a biopsy of the cervical lymph node involved, which was not done due to reasons out of our reach.